Wisdom and Torah : the reception of "Torah" in the wisdom literature of the Second Temple period - Schipper, Bernd Ulrich, 1968-; Teeter, David Andrew.; Schipper, Bernd Ulrich, 1968- (Supplements to the Journal for the Study of Judaism, 2013)
A proper assessment of the manifold relationships that obtain between "wisdom" and "Torah" in the Second Temple Period has fascinated generations of interpreters. The essays of the present collection seek to understand this key relationship by focusing attention on specific instances of the reception of "Torah" in Wisdom literature and the shaping of Torah by wisdom. Taking the concepts of wisdom and torah in the various literary strata of the book of Deuteronomy as a point of departure, the remainder of the book examines the relationship between wisdom and Torah in Wisdom literature of the Second Temple period, including Proverbs, Qohelet, Ps 19 and 119, Baruch, Ben Sira, Wisdom, sapiential and rewritten scriptural texts from Qumran, and the Wisdom of Solomon.